Insurance and risk management for disruptions in social, economic and environmental systems : decision and control allocations within new domains of risk - Grima, Simon; Özen, Ercan; Gonzi, Rebecca Dalli (Emerald studies in finance, insurance, and risk management, 2022)
Challenges destabilize the norm and create distresses and disruptions in, for example, the culture, the technology, regulations, the environmental, etc. that influence the pace of finance and economic activities. This book is a collection of 13 chapters and studies about Insurance and Risk management in response to disruptions caused by social, economic, and environmental challenges to try and stabilize the economy in an effort to ensure sustainability. Insurance and Risk Management for Disruptions in Social, Economic and Environmental Systems brings together studies from scholars, researchers and professionals with different disciplinary backgrounds to highlight discuss and exchange ideas on these challenges, which may seem a danger, but offer prospects for economic and business development. Books in the Emerald Studies In Finance, Insurance, And Risk Management series collect quantitative and qualitative studies in areas relating to finance, insurance, and risk management. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.